Recent development in the preservation effect of lactic acid bacteria and essential oils on chicken and seafood products - Sharma, Heena; Fidan, Hafize; Özogul, Fatih; Rocha, João Miguel (Frontiers in Microbiology, 2022)
Chicken and seafood are highly perishable owing to the higher moisture and unsaturated fatty acids content which make them more prone to oxidation and microbial growth. In order to preserve the nutritional quality and extend the shelf-life of such products, consumers now prefer chemical-free alternatives, such as lactic acid bacteria (LAB) and essential oils (EOs), which exert a bio-preservative effect as antimicrobial and antioxidant compounds. This review will provide in-depth information about the properties and main mechanisms of oxidation and microbial spoilage in chicken and seafood. Furthermore, the basic chemistry and mode of action of LAB and EOs will be discussed to shed light on their successful application in chicken and seafood products. Metabolites of LAB and EOs, either alone or in combination, inhibit or retard lipid oxidation and microbial growth by virtue of their principal constituents and bioactive compounds including phenolic compounds and organic acids (lactic acid, propionic acid, and acetic acid) and others. Therefore, the application of LAB and EOs is widely recognized to extend the shelf-life of chicken and seafood products naturally without altering their functional and physicochemical properties. However, the incorporation of any of these agents requires the optimization steps necessary to avoid undesirable sensory changes. In addition, toxicity risks associated with EOs also demand the regularization of an optimum dose for their inclusion in the products.